# 4x^2-11x-3=0

## Simple and best practice solution for 4x^2-11x-3=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 4x^2-11x-3=0 equation:

Simplifying 4x^{2}+ -11x + -3 = 0 Reorder the terms: -3 + -11x + 4x^{2}= 0 Solving -3 + -11x + 4x^{2}= 0 Solving for variable 'x'. Factor a trinomial. (-1 + -4x)(3 + -1x) = 0## Subproblem 1

Set the factor '(-1 + -4x)' equal to zero and attempt to solve: Simplifying -1 + -4x = 0 Solving -1 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -4x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -4x = 0 + 1 -4x = 0 + 1 Combine like terms: 0 + 1 = 1 -4x = 1 Divide each side by '-4'. x = -0.25 Simplifying x = -0.25## Subproblem 2

Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3## Solution

x = {-0.25, 3}

### See similar equations:

| 3(x-2)-4x=2(x+22)-5 | | 6x+31=13x-64 | | 6x+31=13x-25 | | 2(a-1)=8a-6 | | -8n+2=13-30n | | 0.19y+0.08(y+9000)=3150 | | 4+7x=58+x | | 11x-50=5x-12 | | 30c+50d=290 | | h^2+10h-336=0 | | 11x-150=5x-12 | | 5x+32=12x-31 | | 6x+11x=76+x | | 5.7q-1.7-4.8q=0.1q-1.1 | | 3(5x-4)=18 | | -3(4b+1)+(13b-3)=0 | | 2x+2[x-6]=47 | | 97-3x=4x+6 | | 4x+11=-77-7x | | 11-7x=29-14x | | 5(-2)4= | | 48+5y=96-3y | | P=c+4b+4a | | 5(-2)= | | -8.7=69.6 | | 5x-4x+2=-3 | | 6x+62=11x+2 | | m^2-2m=0 | | 7x^2+1x-5=0 | | 6x+37=16x-83 | | 6x-3y=21 | | -4m+5.5=9.5 | | X^2+15x-81=0 | | 4(x+2)+1=7x-3(x-2) | | 4a+8-2(3+a)= | | 7y-16y-2=4 | | 9x+7=61 | | w^2+3w+4=0 | | 3x^3-6x^2-24x=0 | | 2z^2+14z+20=0 | | 3m+8=34 | | x^4+2x^3-8x-16=0 | | 20z^2=80z+100 | | y^3-2y^2-3y=0 | | 5z^3+20z^2=105z | | x^4+2x^3=3x^2 | | z^4=256 | | 18x^2+18x=-2 | | 50=15-6(-5+2x) | | 8x+7=2x+49 | | n^3-3n^2-n+3=0 | | z^3-3z^2+z-3=0 | | 10x-27=6x+1 | | 9x+7y=2 | | 6x+15=19+x | | z-(-8)=2 | | 4*-4= | | 3x^2=4x+18 | | g-(-2)=7 | | -2x^2+31=2x^2-17 | | m-(-4)=4 | | m-(-2)=9 | | 5x+26=14x-28 | | x-(-3)=2 | | 81-x^2=0 |